Survival benefit of surgical treatment for patients with stage IVB endometrial cancer: a propensity score-matched SEER database analysis - Yixin Zhang; Zhimin Hao; Sufen Yang (Taylor & Francis Group, 2023)
The study aimed to evaluate the value of cancer-directed surgery (CDS) in improving the prognosis of patients with stage IVB endometrial cancer (EC) and under which kind of conditions could maximise its value. The Surveillance, Epidemiology, and End Results database was used to analyse patients diagnosed with stage IVB EC who received chemotherapy between 2004 and 2016. Among 1978 patients were enrolled following propensity score matching (PSM). We found that CDS was closely associated with prolonged overall survival. Moreover, CDS can effectively improve the survival rate of patients with protective or unfavourable factors and should be considered in a range of circumstances. Almost all patients (96.15%) who received surgery were operated on primary tumours of the reproductive organs and obtained favourable surgical outcomes. In conclusion, surgery can improve the survival of patients with stage IVB EC, palliative hysterectomy is worth considering in such patients.IMPACT STATEMENT What is already known on this subject? Patients with stage IVB EC account for a small proportion, so previous researches usually had an insufficient sample size. And it is still controversial whether to perform surgery on patients with stage IVB EC. What do the results of this study add? We verified the value of CDS in improving prognosis of patients with stage IVB EC. We also found that surgery outcomes were better in patients aged ˂ 60 years, and with T1 and T2 invasion. Moreover, resection of the primary site played an important role in prolonging survival time. What are the implications of these findings for clinical practice and/or further research? Surgical treatment can prolong the overall survival of patients with stage IVB EC, even if only primary site resection is performed. Surgery should be more aggressive in patients aged ˂ 60 years, and with lesions confined in the pelvis (with T1 and T2 invasion). The survival rate of patients with brain metastasis may also be improved by surgery. However, because of the small sample size, the surgical benefit needs further confirmation.